Gene essentiality profiling reveals a novel determinant of stresses preventing protein aggregation in Salmonella. Issue 1 (31st December 2022) - Wang, Zuoqiang; Zhu, Siqi; Li, Congcong; Lyu, Lin; Yu, Jingchen; Wang, Danni; Xu, Zhihong; Ni, Jinjing; Gao, Beile; Lu, Jie; Yao, Yu-Feng
ABSTRACT: Adaptation to various stresses during infection is important for Salmonella Typhimurium virulence, while the fitness determinants under infection-relevant stress conditions remain unknown. Here, we simulated conditions Salmonella encountered within the host or in the environment by 15 individual stresses as well as two model cell lines (epithelium and macrophage) to decipher the genes and pathways required for fitness. By high-resolution Tn-seq analysis, a total of 1242 genes were identified as essential for fitness under at least one stress condition. The comparative analysis of fitness determinants in 17 stress conditions indicated the essentiality of genes varied in different mimicking host niches. A total of 12 genes were identified as fitness determinants in all stress conditions, including recB, recC, and xseA (encode three exonuclease subunits necessary for DNA recombination repair) and a novel essential fitness gene yheM . YheM is a putative sulfurtransferase subunit that is responsible for tRNA modification, and our results showed that Salmonella lacking yheM accumulated more aggregates of endogenous protein than wild-type. Moreover, we established a scoring scheme for sRNA essentiality analysis and found STnc2080 of unknown function was essential for resistance to LL-37. In summary, we systematically dissected Salmonella gene essentiality profiling and demonstrated the general and specific adaptive requirements in infection-relevant niches. Our data not only provide valuable insights on how Salmonella responds to environmental stresses during infections but also highlight the potential clinical application of fitness determinants in vaccine development.